Invisíveis: uma etnografia sobre identidade, direitos e cidadania nas trajetórias de brasileiros sem documento - Escóssia, Fernanda Melo da (2019)
This thesis is an ethnography about Brazilians who lived without any kind of documentation until the moment they looked for a free public service of emission of birth certificate installed in a bus in Praça Onze, in the center of Rio de Janeiro. The bus service is the result of a partnership between two projects of the Rio de Janeiro State Court of Justice (TJRJ), the Traveling Justice and the Sepec (Service for the Promotion and Eradication of Birth Registration and the Search for Certificates). The thesis is the result of two years of fieldwork on this bus, accompanying some of its users outside of it as well. In a dialogue with the concept of the "margins of the state" proposed by Das and Poole (2004), it shows how undocumented people disregard themselves as subjects, examining the reasons that led them to seek the birth certificate and interrogating the meanings they attribute to this document. Such an approach allows us to reflect on the role of the document as a key to state control, but also for access to rights. Drawing from life histories, the work describes the so-called "counter syndrome" (when one has to go from one counter to another), detailing the intricacies of the search for documentation in the state bureaucratic framework by bus users. Furthermore, it reconstitutes judicial hearings in which, faced with the absence of the document, undocumented persons construct the truth of their existence before a judge in order to prove that they are, in fact, who they claim to be, and presents narratives of the judges about the services they render on the bus. In a dialogue with Bourdieu (1996), the thesis also analyzes the birth certificate as a result of a rite of institution and inquires the capacities attributed to the document by the users, in a search that is not only an official paper, but also for rights, citizenship and for one’s own history.